2012
DOI: 10.1089/rej.2012.1349
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine and Spermine Are Enriched in Whole Blood of Nona/Centenarians

Abstract: Polyamines (putrescine, spermidine, and spermine) are a family of molecules that derive from ornithine through a decarboxylation process. They are essential for cell growth and proliferation, stabilization of negative charges of DNA, RNA transcription, translation, and apoptosis. Recently, it has been demonstrated that exogenously administered spermidine promotes longevity in yeasts, flies, worms, and human cultured immune cells. Here, using a cross-sectional observational study, we determined whole-blood poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 32 publications
5
69
0
2
Order By: Relevance
“…We first confirmed that spermidine induces autophagy in T cells in vitro in a dose and time-dependent manner shown by increased levels of LC3-II (Figure 6D). Spermidine levels in the blood are known to decrease with age (Pucciarelli et al, 2012). To mimic this, we used the inhibitor of the natural spermidine synthesis pathway DFMO in the human Jurkat T cell line and found that autophagy levels detected by LC3 western blot significantly dropped in BafA treated samples and untreated samples (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
“…We first confirmed that spermidine induces autophagy in T cells in vitro in a dose and time-dependent manner shown by increased levels of LC3-II (Figure 6D). Spermidine levels in the blood are known to decrease with age (Pucciarelli et al, 2012). To mimic this, we used the inhibitor of the natural spermidine synthesis pathway DFMO in the human Jurkat T cell line and found that autophagy levels detected by LC3 western blot significantly dropped in BafA treated samples and untreated samples (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous spermidine concentrations decrease as the organism age, including in humans with the exception of centenarians (Pucciarelli et al, 2012). Acute injections of spermidine in mice activate autophagy in multiple organs (Morselli et al, 2011) while chronic spermidine feeding promotes increase in healthspan (Eisenberg et al, 2009).…”
Section: Pharmacological Anti-aging Interventionsmentioning
confidence: 99%
“…This protective effect has not been shown for other sirtuins (Dillin & Kelly, 2007) which, as occurs with the sirtuin 2, may even promote the cell death in animal models of PD (Outeiro et al ., 2007). Other agents that could be useful for modulating both aging and PD are the insulin growth factors (Mattson et al ., 2004; de Cabo et al ., 2014; Numao et al ., 2014), spermidine (Pucciarelli et al ., 2012; De La Hera et al ., 2013), metformin (Patil et al ., 2014), and rapamycin (Malagelada et al ., 2010; Liu et al ., 2013). …”
Section: Genetic Control Of Pd and Agingmentioning
confidence: 99%